A brief discussion of aspects in breast cancer research, science mentorship and the workplace culture today. (August 2017) - Abderrahman, Balkees
Balkees Abderrahman speaks to Roshaine Wijayatunga, managing commissioning editor: Balkees Abderrahman is a Fellow of Breast Medical Oncology at MD Anderson Cancer Center and a Fellow of the Royal Society of Medicine of Great Britain. She is a PhD trainee under model " Applicants of Very High Quality " at the Faculty of Medicine, The University of Leeds, West Yorkshire, Great Britain. She works with Professor V Craig Jordan, OBE, FMedSci. Dr. Abderrahman is the author of " Steroid Receptors in Breast Cancer, The Breast: Comprehensive Management of Benign and Malignant Diseases 2017 ", " Hormones and Cancer, Oxford Textbook of Cancer Biology 2018 ", " First Targeted Therapy – History of Tamoxifen, Estrogen Receptor and Breast Cancer, Cancer Drug Discovery and Development, Springer Nature 2018 " and " Selective Estrogen Receptor Modulators (SERMs), Estrogen Receptor and Breast Cancer, Cancer Drug Discovery and Development, Springer Nature 2018 ". She has published several articles in breast cancer research. She is also the author of " Love at the Gate " and " Oliver and the Rock " and a contributor at Nature, the Pharmaceutical Journal of the Royal Pharmaceutical Society of Great Britain, The Independent, The American Society of Clinical Oncology (ASCO) Post, The Huffington Post, US News and World Report, The Hill and The Nation . She was a finalist for the Outstanding Youth Award at the United Nations from over 86 countries for " Her outstanding work in tackling some of our greatest social, economic, and environmental challenges ".